Pogrzeb i grób w tradycjach o patriarchach zawartych w Księdze Rodzaju. Stan badań - Basiuk, Maciej (Poznańskie Studia Teologiczne, 2020)
In the sanctuary dedicated to the patriarchs in Hebron, according to tradition, there are graves of Abraham, Isaac and Jacob and their wives, Sarah, Rebekah and Leah. The roots of this tradition go back to the Book of Genesis, however, today there are some people who call into question the credibility of this message. On the grounds of analysis of the text describing the circumstances of Jacob’s death, some state that actually his grave has a diff erent location. Others, in turn, will point out that the story of Abraham purchasing a fi eld with the cave of Machpelah for the grave of Sarah (cf. Gen 23) is a very late tradition, which was attached to the pre-existing text. Therefore, in this article, we will analyze existing studies referring to the issue of the patriarchs’ death and its accom-panying events (funeral, mourning, grave) in order to check how they discuss it and to what extent they approach this practice globally.